The Colombian State and Financial Liability for the Environment: A Case Study of Mining in Zaragoza, Colombia - Cabrera Suárez, Lizandro Alfonso (DIXI, 2014)
This article, based on the legal theory of liability, analyzes unlawful damage and reparation in the proceedings involving illegal gold-mining exploitation in the township of Zaragoza, Buenaventura, Valle del Cauca, Colombia. It specifically analyzes liability attributable to the public administration at its different levels. The article looks at the two main theoretical currents of liability (objective and subjective), recognizing the legislative and jurisprudential evolution from a concept of liability centered on the subjective fault element, towards a concept of liability based on the damage factor, on the objective consequence, which was incorporated at the constitutional level by the 1991 Constituent Assembly. In article 90, this Constitution establishes the Financial Liability of the State, without requiring the elements of a fault, from which it may be inferred that liability for environmental damages is objective because there is no element of fault necessary for its predication. Because the mining exploitation is illegal, there has been a crime committed along with environmental damage not protected under the law and so the research will analyze the type of damage caused. The aim is best to determine whether the case involves pure damage or consecutive damage, due to improper, unregulated and prohibited use of renewable or nonrenewable natural resources without the respective permits, authorizations or licenses .
Keywords: environment; damage; illegal mining; reparation; liability.